2015
DOI: 10.11604/pamj.2015.21.101.6437
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic of plasmodium falciparum chloroquine resistance transporter gene Pfcrt K76T mutation five years after withdrawal of chloroquine in Burkina Faso

Abstract: We investigated the evolution of Pfcrt K76T mutation five years after the withdrawal of chloroquine in Burkina Faso. A total of 675 clinical isolates collected from October 2010 to September 2012 were successfully genotyped. Single nucleotide polymorphism in Pfcrt (codon 76) gene was analyzed. The prevalence of resistant Pfcrt 76T allele was 20.55%. There was a progressive decrease of the proportion of mutant type pfcrt T76 from 2010 to 2012 (X2=5.508 p=0.0189). Our results suggest a progressive return of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
7
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 10 publications
7
7
2
1
Order By: Relevance
“…Despite the implementation of ACT and the withdrawal of chloroquine, the frequency of the resistant allele 76T remained high in Franceville (93.8% in 2004, 96% in 2009, and from 70.6% to 96.3% between 2011 and 2014) and in all of Gabon (100% from 1995 until 2002, 97% from 2005 until 2007, and above 70% since 2008) 25,27,28,38. Recent studies conducted in Gabon from 1995 to 2008 showed an increased but non-significant amount of the wild-type allele K76, as shown in other studies in Sub-Saharan Africa 27,28,4446. In South Gabon, the frequency of the resistant allele 76T was higher at 2009 47.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Despite the implementation of ACT and the withdrawal of chloroquine, the frequency of the resistant allele 76T remained high in Franceville (93.8% in 2004, 96% in 2009, and from 70.6% to 96.3% between 2011 and 2014) and in all of Gabon (100% from 1995 until 2002, 97% from 2005 until 2007, and above 70% since 2008) 25,27,28,38. Recent studies conducted in Gabon from 1995 to 2008 showed an increased but non-significant amount of the wild-type allele K76, as shown in other studies in Sub-Saharan Africa 27,28,4446. In South Gabon, the frequency of the resistant allele 76T was higher at 2009 47.…”
Section: Discussionsupporting
confidence: 56%
“… 25 , 27 , 28 , 38 Recent studies conducted in Gabon from 1995 to 2008 showed an increased but non-significant amount of the wild-type allele K76, as shown in other studies in Sub-Saharan Africa. 27 , 28 , 44 46 In South Gabon, the frequency of the resistant allele 76T was higher at 2009. 47 There can be a long delay in the selection of the T76 Pfcrt genotype, as shown in previous data from Zanzibar, where this selection was not observed in 2005 but clearly appeared in 2009.…”
Section: Discussionmentioning
confidence: 99%
“…In Cape Verde it possibly reflects the limited recombination opportunity, due to the very low malaria transmission over the recent decades. Nevertheless, the identification of the wild-type allele K76 is in line with findings in other malaria regions, where AL is the predominant ACT [ 33 36 ]. Probably, due to lumefantrine, regimens tend to select wild-type pfcrt alleles [ 37 39 ].…”
Section: Discussionsupporting
confidence: 86%
“… 2003 NR NR 2.4% (7/294) 16% NR 35.4% 18.7% Some et al [ 78 ] 2005 NR NR NR NR NR 70.8% NR Thomsen et al [ 16 ] 2002 90% NR NR NR 35.8% (59/165) 28.8% NR Raman et al [ 17 ] 2002 96.1% NR NR 16% NR NR NR Duah et al [ 25 ]. 2005 2003: 50–98% 2003: 48–98% NR NR NR 2010: 40–80% 2010: 35% Sondo et al [ 79 ] 2005 NR NR 20.5% (120/584) NR NR NR NR NR not reported, PC policy change, CQ chloroquine, BF before, AF after …”
Section: Resultsmentioning
confidence: 99%